Breast Cancer Knowledge and Decisions Made for Contralateral Prophylactic Mastectomy: A Survey of Surgeons and Women in the General Population. Issue 5 (May 2019) - Hooper, Rachel C.; Hsu, Jessica; Duncan, Anthony; Bensenhaver, Jessica M.; Newman, Lisa A.; Kidwell, Kelly M.; Chung, Kevin C.; Momoh, Adeyiza O.
Abstract : Background: Decisions made to undergo contralateral prophylactic mastectomy, in women at low risk for bilateral disease, are often attributed to a lack of knowledge. This study examines the role knowledge plays in determining surgical treatment for unilateral breast cancer made by laywomen and surgeons for themselves or loved ones. Methods: The study cohort had three groups: (1) laywomen in the general population, (2) breast surgeons, and (3) plastic surgeons. Laywomen were recruited using Amazon Mechanical Turk Crowd Sourcing. Breast and plastic surgeons from nine states were sent electronic surveys. Demographic and contralateral prophylactic mastectomy–specific data on decisions and knowledge were collected and analyzed. Results: Surveys from 1333 laywomen, 198 plastic surgeons, and 142 breast surgeons were analyzed. A significantly greater proportion of laywomen in the general population favored contralateral prophylactic mastectomy (67 percent) relative to plastic (50 percent) and breast surgeons (26 percent) ( p < 0.0001). Breast surgeons who chose contralateral prophylactic mastectomy were younger ( p = 0.044) and female (0.012). On assessment of knowledge, 78 percent of laywomen had a low level of breast cancer knowledge. Laywomen with higher levels of breast cancer knowledge had lower odds of choosing contralateral prophylactic mastectomy (OR, 0.37; 95 percent CI, 0.28 to 0.49). Conclusions: Fewer women are likely to make decisions in favor of contralateral prophylactic mastectomy with better breast cancer–specific education. A knowledge gap likely explains the lower rates with which surgeons choose contralateral prophylactic mastectomy for themselves or loved ones; however, some surgeons who were predominantly young and female favor contralateral prophylactic mastectomy. Improving patient education on surgical options for breast cancer treatment is critical, with well-informed decisions as the goal. Abstract : Supplemental Digital Content is available in the text.This and Related "Classic" Articles Appear on Prsjournal.com for Journal Club Discussions.